2007
DOI: 10.1586/17446651.2.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Y2, Y4 receptors and obesity

Abstract: The neuropeptide Y system -comprising neuropeptide Y, peptide YY, pancreatic polypeptide and the Y receptors through which they act (Y1, Y2, Y4, Y5 and y6) -has been at the center of attention with regards to regulation of feeding behavior and its possible involvement in obesity. In the past, research has focused mainly on the orexigenic and obesogenic action of this system, with Y1 and Y5 receptors being prime candidates as mediators of neuropeptide Y-induced hyperphagia and obesity. However, in recent years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…We previously reported that the synergy between Y2 and Y4 receptors in reducing adiposity may be related to differential effects on the hypothalamo-pituitary-somatotropic and -gonadotropic axes [23,24], both of which are inhibited by NPY [3]. In two conditions of elevated hypothalamic NPY expression (24-h fasting and leptin-deficient obesity) [12], germline or hypothalamus-specific Y2-but not Y4-receptor deletion prevents the associated decrease in activity of the somatotropic axis, whereas Y4-but not Y2-receptor deletion prevents the associated decrease in activity of the gonadotropic axis [13,14,23].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the synergy between Y2 and Y4 receptors in reducing adiposity may be related to differential effects on the hypothalamo-pituitary-somatotropic and -gonadotropic axes [23,24], both of which are inhibited by NPY [3]. In two conditions of elevated hypothalamic NPY expression (24-h fasting and leptin-deficient obesity) [12], germline or hypothalamus-specific Y2-but not Y4-receptor deletion prevents the associated decrease in activity of the somatotropic axis, whereas Y4-but not Y2-receptor deletion prevents the associated decrease in activity of the gonadotropic axis [13,14,23].…”
Section: Discussionmentioning
confidence: 99%
“…In part, this may be due to the redundancy of the peptides mediating energy homeostasis, thereby limiting the approach of targeting a single pathway in an attempt to reduce food intake and body weight. In addition, central and peripheral Y receptors can have opposing actions on parameters that affect energy homeostasis [54], so it is important to consider which receptor pool a pharmacological agent reaches. Agents that target more than one Y receptor, such as the Y2 and Y4 receptors, may prove to be more effective in inducing weight loss in clinical studies [12].…”
Section: Neuropeptide Y (Npy) -The 'Missing Link' Be-tween Insulin Rementioning
confidence: 99%
“…Of these, Y1 and Y5 are generally believed to be involved in both food intake and energy expenditure, although recent literature suggests the involvement of the Y2 and Y4 subtypes as well. 14 The pharmacology of the Y1 receptor has been studied using potent and selective Y1 receptor antagonists (Figure 1). The effect of NPY administration in Y5 knockout mice was completely blocked by coinjection of the peptidic Y1 antagonist, 1229U91.…”
mentioning
confidence: 99%
“…Five NPY receptors (Y1–Y5) have been cloned and expressed. Of these, Y1 and Y5 are generally believed to be involved in both food intake and energy expenditure, although recent literature suggests the involvement of the Y2 and Y4 subtypes as well . The pharmacology of the Y1 receptor has been studied using potent and selective Y1 receptor antagonists (Figure ).…”
mentioning
confidence: 99%